Socioeconomic inequality in preterm birth in four Brazilian birth cohort studies - Ana Daniela Izoton de Sadovsky; Alicia Matijasevich; Iná S. Santos; Fernando C. Barros; Angelica Espinosa Miranda; Mariangela Freitas Silveira
Abstract Objective: To analyze economic inequality (absolute and relative) due to family income in relation to the occurrence of preterm births in Southern Brazil. Methods: Four birth cohort studies were conducted in the years 1982, 1993, 2004, and 2011. The main exposure was monthly family income and the primary outcome was preterm birth. The inequalities were calculated using the slope index of inequality and the relative index of inequality, adjusted for maternal skin color, education, age, and marital status. Results: The prevalence of preterm births increased from 5.8% to approximately 14% (p-trend < 0.001). Late preterm births comprised the highest proportion among the preterm births in all studies, although their rates decreased over the years. The analysis on the slope index of inequality demonstrated that income inequality arose in the 1993, 2004, and 2011 studies. After adjustment, only the 2004 study maintained the difference between the poorest and the richest subjects, which was 6.3 percentage points. The relative index of inequality showed that, in all studies, the poorest mothers were more likely to have preterm newborns than the richest. After adjustment for confounding factors, it was observed that the poorest mothers only had a greater chance of this outcome in 2004. Conclusion: In a final model, economic inequalities resulting from income were found in relation to preterm births only in 2004, although a higher prevalence of prematurity continued to be observed in the poorest population, in all the studies.